Оцінювання невизначенності вимірювання при калібруванні еталонних перетворювачів тиску - Козлов, Ю. В.; Унгер, В. М. (ХНУРЕ, 2025)
The procedure for estimating the measurement uncertainty during the calibration of reference pressure transducers is considered. The measurement model is defined as the deviation of the transducer readings from the pressure set by the reference. The measurement model takes into account corrections for the resolution of the pressure transducer, the zero error, and the deviation of the temperature at the calibration site from the normalized temperature. The full standard uncertainty and the expanded uncertainty are calculated taking into account the kurtosis of the input values. A calculated measurement uncertainty budget.
Keywords: калібрування; перетворювач тиску